‘Turmeric’ An Age-Old Panacea for many ills can be a Potential Source of Antidermatophytic Agent - Archana Verma3, R. K. Mishra4, A. Dikshit5 , Om Prakash6 and Neetu Shukla7, Amritesh C. Shukla1*, Awadhesh Kumar2, (Journal of Experimental Sciences, 2011)
Antimicrobial evaluation of the essential oil(s) of some spp. of Curcuma viz., CurcumaÃ‚Â  angustifolia, C. aromatica and C. zedoaria Ã¢â‚¬â€œ Ã¢â‚¬Å“an age old panacea for many illsÃ¢â‚¬Â, were screened against three common dermatophytic fungi causing ringworm infection in human beings. The essential oil of Curcuma aromatica Salisb.(Family- Zingiberaceae) was found strongest toxicant against the test fungi. The minimum inhibitory concentration (MIC) of the oil was 1.8Ã‚Âµl/ml against Epidermophyton floccosum and Trichophyton rubrum, and 1.6Ã‚Âµl/ml against Microsporum gypseum; however, it was fungicidal at 2.0 Ã‚Âµl/ml against E. floccosum and T. rubrum, and 1.8 Ã‚Âµl/ml against M. gypseum, respectively. The efficacy contains heavy doses of inoculums (25 discs of 5 mm each.). The (MKT) of the oil was 30 sec against E.Ã‚Â  floccosum & Microsporum gypseum and 20 sec against T. rubrum, while, its MFCs required 6.30 hrs against E.Ã‚Â  floccosum & Microsporum gypseum and 5.30 hrs against T. rubrum. The oils efficacy was thermo stable up to 100 0C and for 36 months of storage, the maximum unit taken into consideration. Moreover, the oil of C. aromatica did not exhibit any adverse effect on mammalian skin up to 5% conc. Relationship of the dermatophytes to the toxicity of the oil vis-a vis phylogeny using molecular data of the pathogens have also been discussed. Further, the clinical trial of the oil in the form of ointment (at 1% v/v conc) to topical testing on patients, attending out patient department (OPD) of MLN Medical College, Allahabad is still in progress.